Social media marketing communication and consumer-based brand equity: an account of automotive brands in Malaysia - Raji Ridwan Adetunji,; Sabrina Mohd Rashid,; Mohd Sobhi Ishak, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Achieving brand equity are top priorities for many organizations because brand is one of the most prized assets of any organization. As such, the academia continues to exert considerable efforts on understanding the factors that influence the development of brand equity. For instance, previous studies have demonstrated that social media communication has significant impact on Consumer-Based Brand Equity (CBBE), however, researchers have not really focused on the relationships of several types of marketing communications anchored by different social media platforms for brand equity. As such, the objective of this study is to examine the relationships between the social media marketing communications, specifically, user-generated type (Social Media Word-of-Mouth) and firm created types (Social Media Advertising, Social Media Promotion and Social Media Interactive Marketing); and the CBBE of automotive brands in Malaysia. Subsequently, 800 samples were selected through cluster samplings from five cities in five geographical regions across Malaysia. Survey questionnaires were administered to users of four types of automotive brands, namely; PROTON, PERODUA, TOYOTA and HONDA. The data collected was analyzed using descriptive statistics, correlation and multiple regressions in SPSS 22. The findings revealed that, the selected automotive brands have notable presence on Facebook, YouTube, Instagram and Twitter. Furthermore, it was found that, social media advertising, social media promotions and social media word-of-mouth have positive relationships with the CBBE of automotive brands. However, social media interactive marketing has an insignificant role in the CBBE. The theoretical and practical implications of the findings are discussed in this paper.